2015
DOI: 10.1097/meg.0000000000000375
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric surgery and nonalcoholic fatty liver disease

Abstract: The rising prevalence of nonalcoholic fatty liver disease (NAFLD) is associated with the increasing global pandemic of obesity. These conditions cluster with type II diabetes mellitus and the metabolic syndrome to result in obesity-associated liver disease. The benefits of bariatric procedures on diabetes and the metabolic syndrome have been recognized for some time, and there is now mounting evidence to suggest that bariatric procedures improve liver histology and contribute to the beneficial resolution of NA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 172 publications
(240 reference statements)
0
17
0
Order By: Relevance
“…In fact, emerging evidence from mouse and human studies suggests that modulation of FXR (either in the liver or the intestine) and/or TGR5 may be useful in NAFLD treatment by enhancing insulin secretion and sensitivity, inhibiting lipogenesis, and stimulating oxidation of FAs. Moreover, studies showing that circulating BA levels increase along with the metabolic benefits after bariatric surgery, and that BAs might be involved in NAFLD/NASH reversion in this setting support the concept that variations in serum BA levels and/or composition have relevant metabolic effects. Of note, changes in circulating BAs with potential benefit for NAFLD/NASH can be achieved through modulation of BA transporters or manipulation of GM .…”
Section: Perspectives On Targeting Ba‐related Pathways For the Treatmmentioning
confidence: 71%
“…In fact, emerging evidence from mouse and human studies suggests that modulation of FXR (either in the liver or the intestine) and/or TGR5 may be useful in NAFLD treatment by enhancing insulin secretion and sensitivity, inhibiting lipogenesis, and stimulating oxidation of FAs. Moreover, studies showing that circulating BA levels increase along with the metabolic benefits after bariatric surgery, and that BAs might be involved in NAFLD/NASH reversion in this setting support the concept that variations in serum BA levels and/or composition have relevant metabolic effects. Of note, changes in circulating BAs with potential benefit for NAFLD/NASH can be achieved through modulation of BA transporters or manipulation of GM .…”
Section: Perspectives On Targeting Ba‐related Pathways For the Treatmmentioning
confidence: 71%
“…The relationship between adiponectin and hepatoprotection has been previously observed in the literature (18)(19)(20)(21) . Since bariatric surgery leads to increases in the levels of adiponectin (22)(23)(24)(25) , it is reasonable to suppose that this mechanism is involved to some degree in the significant improvement of NAFLD reported after surgery (26)(27)(28)(29) .…”
Section: Discussionmentioning
confidence: 99%
“…Another meta-analysis, conducted by Bower et al, 156 revealed that bariatric surgery was associated with a significant reduction in the weighted incidence of a number of histological features of NAFLD, including steatosis (50.2%), fibrosis (11.9%), hepatocyte ballooning (67.7%) and lobular inflammation (50.7%); surgery was also associated with a reduction in liver enzyme levels. These authors emphasized that there was high heterogeneity among the methodologies and results, a factor that may have limited their analysis of these findings.…”
Section: Systematic Reviews and Synthesismentioning
confidence: 99%